PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA ORGANISASI DI BADAN PERENCANAAN PEMBANGUNAN DAERAH (BAPPEDA) PROVINSI RIAU - Nursaidah "; Adianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at the Regional Development Planning Agency of Riau Province. With the aim of measuring the influence of organizational culture on organizational performance in the Regional Development Planning Agency (BAPPEDA) of Riau Province. Where the population is all employees of the Riau Provincial Development Planning Agency, which amounts to 160 people. The sample used in this study was 62 people taken using the Slovin formula and processing data using the product moment correlation method with the SPSS program. Based on the test results if the data using product correlation moment can be taken some conclusions, namely the organizational culture of the Regional Development Planning Agency (BAPPEDA) of Riau Province is classified as good which is judged by respondents' responses about indicators of organizational culture, namely: mission, consistency, adaptability, and involvement with values average score of 200 which is in the range of the scale of 188-229 good category. Organizational performance in the Regional Development Planning Agency (BAPPEDA) of Riau Province is classified as good, judging from the responses of respondents about organizational performance indicators, namely: quality, quantity, use of time and collaboration with a score of 208 which is in the range of 188-229 in the good category. Organizational culture has a significant effect on organizational performance in the Regional Development Planning Agency (BAPPEDA) of Riau Province with the closeness of the relationship in the very strong category. Where the results of the correlation test obtained a probability number of 0,000, where 0,000 is smaller than 0.05 (0,000 <0,05), then Ho is rejected, meaning there is a significant relationship between organizational culture and organizational performance. The correlation coefficient produced is equal to 0.832 which is in the range of 00.80-1,000 with a very strong category. The hypothesis (Ha) is accepted and (Ho) rejected.Keywords : Organizational Culture and Organizational Performance